Phospholipids and lipopolysaccharide of Aeromonas hydrophila. - Howard, S P (1985)
The phospholipids and lipopolysaccharide of Aeromonas hydrophila were characterized. Phosphatidylethanolamine and phosphatidylglycerol were the major phospholipid components. The outer membrane contained more phosphatidylethanolamine and less phosphatidylglycerol than the inner membrane, and the phospholipids of the outer membrane contained a higher proportion of saturated fatty acids. Only four fatty acids (C14:0, C16:0, C16:1, and C18:1) were found in the phospholipids. The lipopolysaccharide of A. hydrophila did not contain the eight-carbon sugar 3-deoxyoctulosonic acid nor did it contain C16:0, both of which are typical constituents of the lipopolysaccharide of many other species.